The Effect of Accounting Conservatism, Free Cash Flow and Financial Distress on Company Value - Delima, Anisa; Linawati (Yayasan Sinergi Kawula Muda, 2023)
This research aims to investigate the relationship accounting conservatism , free cash flow, and financial distress on company value. Retrieval method sample in this study uses purposive sampling method, so obtained sample study as many as 21 Consumer Non Cyclicals companies listed on the Indonesia Stock Exchange in 2017-2021. Data analysis was performed with panel data regression with use eviews 10. The findings reveal that in simultaneously test accounting conservatism, free cash flow, and financial distress have an effect to company value. However, Partial Accounting Conservatism and Free Cash Flow do not influential to value of company, while financial distress has an effect to value of companies in consumer non-cyclicals companies.